The Letter Ngain (‘Ain) In The Children’s Ngapak Reading: Study At TPQ At Taqwa In Ayah Village, Kebumen - Hamidah, Wanda Nur; HS, Muhammad Alwi; Faizah, Fatikhatul (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2023)
This article examines the phenomenon of ‘ain being read ngain by ngapak children when reading the Qur'an. This article focuses on the Qur'an Education Park (Taman Pendidikan Al-Qur’an [TPQ]) Ayah village, Kebumen. The problem formulation of this article is how reading ngain as a representation of 'ain in reading the Qur'an among the ngapak children at TPQ At-Taqwa? This article is field research, so the primary data comes from interviews, observations, and documentation at TPQ At-Taqwa. This article uses a descriptive-analytical method with a qualitative approach and applies the theory of Qur'an reception by Ahmad Rafiq, especially functional reception. This article concludes that the pronunciation of ngain in reading the Qur'an among ngapak children in TPQ At-Taqwa Ayah village, Kebumen, is a phenomenon of the interaction of local ngapak Muslims towards the Qur'an which functions to get closer to the Quran. TPQ responds in a dynamic-contextual-based negotiation, which is not rigid and is according to social conditions. At first, the teachers tried to improve the pronunciation of ngain to become 'ain, but then ngain was accepted as a representation of 'ain with a function so that the children in the village could continue to be enthusiastic about reading the Qur'an. The findings of this study offer a humanist approach to the Qur’an by Muslim readings that are different from others so that they do not discriminate and can be tolerant, inclusive, and friendly towards the diversity that exists